The Mainstreaming of Pesantrens and Madrasahs in Indonesia - Jamhari, Jamhari (Studia Islamika, 2005)
The project of this article has focused on six strategic groups in pesantrens and madrasahs. These are: 1)Kyai (male religious leaders) and Nyai (female religious leaders) of pesantren salaf; 2) Kyai and Nyai of pesantren khalaf; 3) key community leaders; 4) principals ofmadrasah aliyahmadrasah aliyah; and 6) student leaders of madrasah aliyah.DOI: 10.15408/sdi.v12i2.593